Investigation on Gasification Reaction Behavior and Kinetic Analysis of Iron Coke Hot Briquette under Isothermal Conditions. Issue 2 (18th October 2018) - Wang, Hongtao; Chu, Mansheng; Guo, Bingyu; Bao, Jiwei; Zhao, Wei; Liu, Zhenggen; Tang, Jue
Abstract : Gasification reaction behavior of iron coke as well as kinetic parameters is extremely important for its quality evaluation and practical application in an actual blast furnace. However, there are few researches on the gasification behavior of iron coke, especially for iron coke hot briquette (ICHB) prepared by hot briquetting process. In this paper, the gasification reaction behavior of ICHB is experimentally investigated under isothermal conditions. Meanwhile, the kinetic analysis for the gasification process of ICHB and the related mechanism are carried out. The results demonstrate that the increase of the reaction temperature causes the significant rise of the carbon conversion rate and the reaction rate of ICHB, while the post‐reaction strength is evidently decreased. The size degradation of ICHB after reaction is increasingly serious as the reaction temperature goes up, and more pores as well as cracks are generated inside the gasified ICHB. During the gasification, the reduction of iron oxide, the oxidization of metal iron, and the generation reaction of fayalite are concomitantly occurred. The most probable mechanism function is confirmed. Based on this model, the activation energy and pre‐exponential factor are conducted, which are 144.77 kJ mol −1 and 999.37 min −1, respectively. Abstract : In this paper, the gasification reaction behavior and kinetic analysis of iron coke hot briquette is experimentally investigated under isothermal conditions. The reaction mechanism of iron coke hot briquette gasified with CO2 is revealed. Simultaneously, the most appropriate mechanism function for iron coke hot briquette gasification is confirmed and the kinetic parameters are conducted.